The Immediate Adverse Events of Lumbar Interventional Pain Procedures in 4209 Patients; an Observational Clinical Study - (:unkn) unknown (My University, 2021)
OBJECTIVE: Lumbar interventional pain procedures (LIPP) are frequently used in low back pain and show an increasing trend in recent years. LIPP are highly effective when performed by properly trained physicians. However, some adverse events are seen during interventional procedures. Our aim in this study is to determine the immediate adverse events rates of LIPP and to inform our colleagues about possible adverse events. STUDY DESIGN: Retrospective, observational study. SETTING: A university hospital pain management center. METHODS: After approval of the institutional ethics committee, a retrospectively evaluation of patients, who received fluoroscopy guided LIPP between January 2015 and December 2020, were performed. This observational study was conducted with 4209 patients who underwent LIPP including epidural steroid injections, sacroiliac and facet joint injections, medial branch blocks or RF, dorsal root ganglion pulse RF, epidural catheter or spinal cord stimulator applications. RESULTS: No major adverse events were detected during the procedures. Minor adverse events were detected in a 60 patients and adverse events rate was found to be 1.4% (95% confidence interval [CI]: 1.0-1.8%). Minor adverse events rates vary between 0.7-2.3% according to the procedures type. The most common adverse events was determined as vasovagal reactions (26/60). Facial numbness, cramps, and seizures were detected as rare adverse events. CONCLUSION: There were no major adverse events were seen during 4209 patients. The rate of minor adverse events were 1.4% with no sequelae in any of the events. When evidence-based guidelines are followed, interventional pain procedures are performed safely.
Keywords: Spine; safety; fluoroscopy; back pain; lumbar